Language Attitude In Learning Interaction At SMK Negeri 1 Pinrang - Hestiaty, Hestiaty; Munirah, Munirah; Adam, Andi (Journal of Educational Sciences, 2025)
This study is a descriptive qualitative research that aims to determine the form of aspects and components of language attitudes, as well as the factors that influence them at SMK Negeri 1 Pinrang. Data were collected through observation, interviews, and documentation, then analyzed using the Miles, Huberman, and Saldana model through the stages of data reduction, data presentation, and conclusion drawing. The results showed that aspects of language attitude include: loyalty and pride of teachers and students who are classified as positive, while aspects of awareness are positive for teachers and negative for students. In the language attitude component, the cognitive component of teachers is positive, but students are negative. Affective and conative components, both teachers and students show negative attitudes. The factors that influence language attitudes consist of internal factors (personal experience, personality, identity, and social cognition) and external factors (family, social environment, mass media, and technology). These findings indicate the need to increase language awareness and strengthen positive attitudes in language use in the school environment.